Clinical Epidemiology Practice and Methods - Barrett, Brendan; Parfrey, Patrick S. 1950- (Humana Press, 2009)
Clinical epidemiology provides the scientific basis for the practice of medicine due to its focus on the diagnosis, prognosis and management of human disease using appropriate research design, measurement and evaluation. In Clinical Epidemiology: Practice and Methods, leading experts contribute selections intended to educate researchers on how best to undertake clinical research. Divided into two categories, the volume first covers issues of design, measurement and analysis associated with various research designs, then continues with methods to better inform medical decision-making, including aggregation of multiple studies using meta-analysis, health economics, clinical practice guidelines and health technology assessment. As a part of the highly successful Methods in Molecular Biology™ series, this comprehensive text collects the kind of detailed, up-to-date information and implementation advice that is crucial for getting optimal results. Essential and advantageous, Clinical Epidemiology: Practice and Methods is an ideal reference for medical practitioners, basic scientists and allied health professionals who desire to improve clinical outcomes
Keywords: Biomedicine; Molecular Medicine; Epidemiology; Biostatistics; Medicine; Molecular biology